2011
DOI: 10.1002/mus.22051
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography and kinematic changes of gait cycle at different cadences in diabetic neuropathic individuals

Abstract: These findings suggest that when diabetic individuals face a new challenging situation that induces a higher demand for muscle strength and propulsion, the necessary range of motion and neuromuscular control around distal joints are insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 36 publications
6
53
1
4
Order By: Relevance
“…This finding is consistent with the EMG results of the triceps surae, which presents a deficit in its activation in locomotor activities 2,[14][15][16] , and it is expected that in a more difficult task that requires more eccentric activity and control, such as descending stairs, the ankle muscles could not respond adequately.…”
Section: Effect Size Classificationsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is consistent with the EMG results of the triceps surae, which presents a deficit in its activation in locomotor activities 2,[14][15][16] , and it is expected that in a more difficult task that requires more eccentric activity and control, such as descending stairs, the ankle muscles could not respond adequately.…”
Section: Effect Size Classificationsupporting
confidence: 79%
“…The ankle plays an important role 12,13 , as its full range of motion allows a suitable distribution of the mechanical energy absorption at the initial foot contact with the step and a proper propulsion at the end of the stance 5 . Ankle function is dramatically affected in diabetic patients since they present a limited range of motion (ROM), lower and delayed triceps surae activity 2,[14][15][16] combined with progressive loss of foot sensitivity. During stair descent, normal ankle ROM and proper muscle eccentric control are even more necessary, and if ankle function is impaired, compensations and adaptations in the kinetics and kinematics of the knee and hip would be expected, as Mueller et al 17 suggested in level gait.…”
Section: Introductionmentioning
confidence: 99%
“…Because the MNSI questionnaire and physical assessment (form) are screening tools, we adopted different and higher cutoff values than those recommended in the literature to be sure to include severe neuropathic patients in our analysis. 5,20,21 The exclusion criteria for all groups were as follows: age over 65 years; partial or total amputation of the foot; Charcot's arthropathy (or any other major orthopedic foot alteration confirmed by radiography); presence of peripheral or central neurological disease not caused by diabetes; presence of retinopathy or nephropathy; plantar ulcers at the time of evaluation; presence of any other musculoskeletal disorder or pain; and use of any assistive devices to walk.…”
Section: Subjectsmentioning
confidence: 99%
“…However, Deschamp et al [24] and Rao et al [25], using slightly different foot models, report a reduction in hindfoot relative to shank excursion during walking in those with DMPN compared to healthy controls. Past work using single segment foot models have been similarly inconsistent when examining motion between the foot segment and the shank [2630]. The source of the inconsistency across studies is not readily apparent.…”
Section: Discussionmentioning
confidence: 99%